2017
DOI: 10.14366/usg.16046
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal diagnosis of aberrant right subclavian artery in an unselected population

Abstract: PurposeThe purpose of this study was to determine the frequency of aberrant right subclavian artery (ARSA) among unselected fetuses and to evaluate its association with chromosomal abnormalities and other congenital anomalies.MethodsIn all, 7,547 fetuses (gestational age, 20 to 34 weeks) were examined using routine antenatal sonography at our institution between April 2014 and September 2015. The right subclavian artery was assessed using grayscale and color Doppler ultrasonography in the transverse 3-vessel a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
2
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 22 publications
3
20
2
6
Order By: Relevance
“…Of 57 studies identified through the electronic search and manual searching of references, 27 were assessed in full text, and of these, 14 were excluded (Table S2). Therefore, 13 studies, encompassing a total of 333 cases of isolated ARSA, were included in the review, of which seven involved retrospective and six prospective data acquisition (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…Of 57 studies identified through the electronic search and manual searching of references, 27 were assessed in full text, and of these, 14 were excluded (Table S2). Therefore, 13 studies, encompassing a total of 333 cases of isolated ARSA, were included in the review, of which seven involved retrospective and six prospective data acquisition (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…The ARSA was not confirmed postnatally. 20,21 and if the arch is a left arch, then there is a very low probability of a vascular ring. 22 Our conclusion is similar to other studies performed in different populations that have shown limited utility for a fetal ECHO following a normal AS.…”
Section: Discussionmentioning
confidence: 99%
“…Review of the images, including Doppler of the ARSA, retrospectively confirmed that the neonatal echocardiogram most likely overlooked this finding due to poor visualization, as a result of lung aeration in the neonate. Some would argue whether an ARSA is important to identify, as when isolated, there is a very low risk for aneuploidy, including trisomy 21 and deletion 22q.11, 20,21 and if the arch is a left arch, then there is a very low probability of a vascular ring 22 …”
Section: Discussionmentioning
confidence: 99%
“…There is a discrepancy in the reported prevalence of ARSA in cadaveric studies in comparison to that in prenatal ultrasound studies, possibly explained by insufficient prenatal detection of this condition. Two large-scale cadaveric studies have reported a prevalence of 1.23–2.2% [ 15 , 16 ], while prenatal ultrasound studies in unselected populations have reported a prevalence of only 0.4% [ 4 , 24 ]. A low ARSA prevalence was also found in additional prenatal studies [ 7 , 18 , 25 ].…”
Section: Discussionmentioning
confidence: 99%